2015
DOI: 10.4238/2015.january.23.4
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of Marmosops and the occurrence of Marmosops pinheiroi (Pine, 1981) (Didelphimorphia, Didelphidae) in the Cerrado savanna of Maranhão, Brazil

Abstract: ABSTRACT. The present study reviews the phylogeny of the genus Marmosops and expands the geographic range of Marmosops pinheiroi to the Brazilian State of Maranhão. Five specimens of M. pinheiroi were collected from the Inhamum Municipal Environmental Protection Area in Caxias, Maranhão. Total DNA was extracted and the mitochondrial cytochrome b gene was sequenced in an ABI PRISM 3500. Additional sequences of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
(38 reference statements)
0
5
0
4
Order By: Relevance
“…In their survey of the bats of the Amazon biome of Maranhão, Bernard et al (2011) recorded 21 species, of which seven were also found in the present study of the state's Cerrado. In the light of the results of the studies of Olímpio et al (2015), Nascimento et al (2015) and Costa et al (2012) the present study presents evidence of the occurrence in the APA Inhamum of species typical of the state's different biomes, in addition to species endemic to the Cerrado, emphasizing the importance of this site for the understanding of the distribution patterns of the region's chiropterans.…”
Section: Discussionmentioning
confidence: 82%
“…In their survey of the bats of the Amazon biome of Maranhão, Bernard et al (2011) recorded 21 species, of which seven were also found in the present study of the state's Cerrado. In the light of the results of the studies of Olímpio et al (2015), Nascimento et al (2015) and Costa et al (2012) the present study presents evidence of the occurrence in the APA Inhamum of species typical of the state's different biomes, in addition to species endemic to the Cerrado, emphasizing the importance of this site for the understanding of the distribution patterns of the region's chiropterans.…”
Section: Discussionmentioning
confidence: 82%
“…In particular, coalescent analyses of nuclear markers could help determine whether any of the several haplogroups of M. bishopi (table 11) are cryptic species. On the other hand, morphological analyses would be welcome in any future attempt to evaluate the taxonomic status of populations with M. pinheiroi-like mtDNA sequences from savanna landscapes in Maranhão (Nascimento et al, 2015), and larger sample sizes would certainly be helpful for testing the statistical significance of morphometric differences inferred from small numbers of specimens in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The specimens that Nascimento et al (2015) identified as Marmosops pinheiroi extend the potential range of this species by almost 700 km, into the Brazilian state of Maranhão. These specimens are also remarkable for having been collected in savanna, whereas all others known to us have been taken in lowland rain forest.…”
Section: Marmosops Pakaraimaementioning
confidence: 99%
See 1 more Smart Citation
“…Although 39 nominal taxa have been referred to Marmosops , many of these names are thought to be synonyms of just 17 currently recognized species (Voss & Jansa, ; Voss et al ., ; García, Sánchez‐Hernández & Semedo, ; Table ). The last comprehensive taxonomic treatment of most of the species now referred to Marmosops was Tate's () monographic revision of ‘mouse opossums’ ( Marmosa sensu lato ), with subsequent publications on the systematics and taxonomy of this group limited to lists of species (Cabrera, ; Gardner & Creighton, ; Gardner, ), descriptions of new taxa (Handley & Gordon, ; Pine, ; Gardner, ; Voss et al ., ; García et al ., ), re‐descriptions based on newly collected material (Díaz‐N, Gómez‐Laverde & Sánchez‐Giraldo, ), revisions of locally co‐occurring species (Patton, da Silva & Malcolm, ; Voss, Lunde & Simmons, ; Voss, Tarifa & Yensen, ), phylogeographical studies (Mustrangi & Patton, ; Steiner & Catzeflis, ), and phylogenetic analyses based on a few exemplar species (Patton, dos Reis & Da Silva, ; Jansa & Voss, ; Voss & Jansa, , ; Steiner et al ., ; Flores, ; Nascimento et al ., ). To date, no study has attempted to assess the validity of all of the currently recognized species of Marmosops , nor has any phylogenetic analysis included more than 50% of them.…”
Section: Introductionmentioning
confidence: 97%